â€œPERILAKU RISWAHâ€ SEBAGAI RANGSANG CIPTA DALAM KARYA SENI GRAFIS - Wijaya, Reza Sastra (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2019)
Bribery is a familiar phenomenon in the society. This term is often associated as money politics, facilitation payments, etc. This problem becomes entrenched in modern life. It is caused by the impact of economic influence (money) in the modern era.This phenomenon becomes a stimulation and intrigue for artists to express their opinions in the form of aesthetic objects. The observing of various phenomena is an important process in the work as an artist because the phenomenon has a strong disturbance that stimulates artists to produce art. In this case the bribery has a function as an object of stimulation that triggers ideas to produce a work of art in which the idea is processed into print making. This art using two main techniques in print making, those are print relief (high print) and serigrafi (filter printing) techniques. The function of print relief is as a printing master as well as the contour in the art work and serigrafi that has a function in coloring process. The merging of these two techniques is inseparable from the principle of the process of the conventional print making which the entire process refers to the essence that exists in printing techniques.